Preparation method of porous carbonized wood loaded ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst
By using porous carbide wood-supported ruthenium-based hydrotalcite nanosheet electrocatalyst in the anode oxygen evolution reaction, the problems of poor stability and cumbersome preparation process are solved, efficient and stable electrocatalytic performance is achieved, and energy utilization is improved efficiency.
Patent Information
- Application Number
- CN202411834646.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing ruthenium-based electrocatalysts have poor stability in the anode oxygen evolution reaction, the preparation process is cumbersome and requires high-temperature annealing, resulting in low energy utilization efficiency, large interface resistance when used by powder catalysts, and low utilization rate of active materials.
The preparation method of porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen-analysis electrocatalyst is obtained through pretreatment, carbonization, precursor preparation and hydrothermal reaction, and electrocatalysts with high catalytic activity and stability are avoided, and the annealing step and Use of binder.
High catalytic activity and stability at low overpotentials are achieved, excellent electrocatalytic performance, reduce energy consumption of electrolytic reactions, improve energy utilization efficiency, and maintain a three-dimensional ordered porous structure for electrolyte penetration and gas transmission .
Smart Images

Figure CN119287414A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysts, and in particular relates to a method for preparing a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst. Background Art
[0002] In the water electrolysis reaction, the additional potential required for the anodic oxygen evolution reaction (OER) becomes a key factor restricting the energy conversion efficiency because it involves a complex proton-coupled electron transfer process and unfavorable thermodynamic conditions. Therefore, the present invention is committed to reducing the OER overpotential to improve the overall energy utilization efficiency. Ruthenium-based electrocatalysts are regarded as benchmark materials for OER due to their excellent electrocatalytic performance, but their stability under operating conditions is particularly poor. The current mainstream metallic ruthenium (elemental ruthenium and ruthenium alloys), ruthenium-based oxides, ruthenium-based phosphides / chalcogenides and other catalysts have a rather cumbersome preparation process and often involve necessary high-temperature annealing steps. In addition, these catalysts are usually powder-type catalysts, which require the use of binders during use, increase interface resistance, low utilization of active materials and stability issues. Summary of the invention
[0003] The present invention aims to solve the above technical problems and provides a method for preparing a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst. The method is simple and the prepared oxygen evolution electrocatalyst has strong catalytic activity and stability.
[0004] The technical solution of the present invention is: A method for preparing a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst comprises the following steps: (1) Pretreatment: The basswood was cut into wood chips, which were ultrasonically treated with deionized water and ethanol in sequence and then vacuum dried to obtain dry wood chips; (2) Preparation of carbonized wood: pre-carbonizing the dried wood chips and then calcining them under the protection of inert gas to obtain a carbonized wood substrate; (3) Preparation of precursor solution: dissolving nickel nitrate hexahydrate, iron nitrate nonahydrate, ruthenium trichloride and urea in deionized water to obtain a precursor solution; (4) Hydrothermal reaction: The carbonized wood substrate in step (2) and the precursor solution in step (3) are mixed and placed in a high-pressure reactor for hydrothermal reaction. After cooling to room temperature, the product is collected, repeatedly washed with deionized water and ethanol, and dried to obtain a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst.
[0005] In order to remove impurities in the basswood and avoid affecting the subsequent carbonization quality, it is washed with deionized water and ethanol in sequence. Preferably, in the step (1) of the present invention, the solid-liquid ratio of basswood to deionized water or ethanol is 1:20-30 g / ml; in order to better remove impurities in the product and prevent teamwork, it is necessary to wash with deionized water and ethanol in sequence. Preferably, in the step (4), the solid-liquid ratio of the product to deionized water or ethanol is 1:20-30 g / ml; each ultrasonic treatment time is 20~30 min.
[0006] In order to obtain better catalytic activity and catalytic stability, preferably, in step (1) of the present invention, the wood chips are 200-300 mm long, 150-200 mm wide, and 1-2 mm thick. If the wood chips are too large, the pores of the carrier after carbonization will also be relatively long, affecting the diffusion rate of the subsequent catalyst and reducing the performance of the catalyst. If the wood chips are small, it is easy to cause the agglomeration of the hydrotalcite nanosheets, and they may also break or deactivate during the reaction, resulting in reduced catalytic activity.
[0007] In order to improve the carbonization effect, the wood chips need to be pre-carbonized before carbonization. Preferably, in step (2) of the present invention, the dried wood chips are pre-carbonized in air at 200-300°C for 5-6 hours. Pre-carbonization can remove aliphatic structures, moisture and volatile components, providing more favorable conditions for the formation of subsequent carbonization voids.
[0008] In order to improve the hardness and oxidation resistance of carbonized wood and obtain a better carbon carrier, the present invention adds silicon carbide to modify the wood chips during the carbonization process. Preferably, in the step (2) of the present invention, after pre-carbonization, 0.5-1.1% of the weight of the dry wood chips is mixed with the pre-carbonized wood chips, and then calcined under the protection of inert gas. By adding silicon carbide, the hardness of the carbonized wood and the oxidation resistance during carbonization at high temperature can be improved, the structure and activity of the carbonized wood can be effectively protected, and the foundation for the stability of the subsequent catalyst can be laid. However, the amount of silicon carbide added should be moderate. If the amount added is too high, it will interfere with the interaction force of the molecular chains inside the pre-carbonized basswood chips. Excessive silicon carbide may form stress concentration points inside the pre-carbonized basswood chips, resulting in stress cracking, reducing the mechanical strength and stiffness of the basswood after carbonization, thereby affecting the subsequent loading performance and stability of the catalyst; if the amount of silicon carbide added is insufficient, the modification effect on the pre-carbonized basswood chips is not obvious, and the effect of the present invention cannot be achieved.
[0009] In order to obtain a better carbonization effect and improve the mechanical strength and performance of the carbonized wood, preferably, in step (2) of the present invention, the temperature is 900-1100°C and the argon gas rate is 0.8-1.0 L min -1 Calcinate for 5~7 h under the conditions of
[0010] In order to improve the catalytic activity of the electrocatalyst, it is necessary to reasonably prepare the precursor solution. Preferably, step (3) of the present invention is specifically as follows: 0.4-0.8 mmol nickel nitrate hexahydrate, 0.1-0.4 mmol ferric nitrate nonahydrate, 0.04-0.06 mmol ruthenium trichloride and 4-6 mmol urea are dissolved in 30 mL of deionized water and stirred for 20-35 min to obtain a precursor solution.
[0011] In order to improve the performance of the electrocatalyst, preferably, the carbonized wood substrate in step (4) of the present invention and the precursor liquid in step (3) are in a ratio of 0.1:20-30 g / ml. If the ratio of the carbonized wood substrate is too high, the active sites of the catalyst will be reduced, thereby reducing the catalytic efficiency and reaction rate of the catalyst; if the ratio of the carbonized wood substrate is too low, the metal nanoparticles cannot be fully dispersed on the carrier, and agglomeration may occur, reducing the effective surface area of the catalyst, reducing the number of active sites of the catalyst, and reducing the catalytic activity of the catalyst. In addition, the carbonized wood substrate not only provides support, but also helps to stabilize the metal nanoparticles. If the ratio of the carbonized wood substrate is too low, it may cause the loss of active components and affect the stability of the catalyst.
[0012] In order to improve the catalytic activity and stability of the electrocatalyst, preferably, in step (4) of the present invention, the hydrothermal conditions are: reacting at 100-200°C for 10-14h. The hydrothermal conditions of the present invention are mild, so that the active components can be evenly deposited on the pores and surface of the carbonized wood substrate, thereby obtaining a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst with high density.
[0013] Preferably, in step (4) of the present invention, before the precursor solution is mixed with the carbonized wood substrate in step (2), 0.3-0.8% of mannitol by weight of the precursor solution is added and mixed evenly with the precursor solution. In the hydrothermal reaction, as the temperature rises, water may partially volatilize to form bubbles. When the active components are loaded onto the carbonized wood substrate, the bubbles may cause holes or cracks in the catalyst layer, and may also interfere with the uniform distribution of the active components, thereby affecting the mechanical strength and stability of the catalyst, easily causing the catalyst to be deactivated, increasing the amount of dead materials, and affecting the activity of the electrocatalyst. When mannitol is added to the precursor solution, since mannitol has strong permeability, when bubbles appear, it can penetrate into the bubbles, which can reduce the accumulation of bubbles, or even eliminate the bubbles, so that the bubbles quickly leave the precursor solution, enhance the adhesion of the hydrotalcite on the nanosheets on the carbonized wood substrate, make the catalytic activity more evenly attached, ensure the structural integrity of the catalyst, and improve the catalytic activity and stability of the catalyst.
[0014] Due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The electrocatalyst prepared by the method of the present invention is used as an anode catalyst in the electrolysis of water and has good catalytic activity. The OER reaction requires a lower overpotential, which can reach 100 mA cm -2 , and has good stability.
[0015] 2. In the method of the present invention, a carbonized wood substrate with a three-dimensional ordered porous network is used as a catalyst carrier, and a hydrotalcite nanosheet array catalyst grown on the carbonized wood substrate skeleton is obtained through a simple one-step hydrothermal method. The method of the present invention has mild reaction conditions, which can not only retain the three-dimensional ordered porous structure of the wood itself, but also provide a favorable channel for the penetration of electrolyte and gas transmission. In addition, after modification with silicon carbide during carbonization, a large number of nucleation sites are provided for the growth of hydrotalcite nanosheets, thereby avoiding the occurrence of agglomeration in the nucleation and growth process of nanoparticles, and realizing uniform and dense growth of nanosheets.
[0016] 3. When preparing the electrocatalyst by the method of the present invention, adding silicon carbide during the carbonization process of the wood chips can improve the hardness and oxidation resistance of the wood chips and prevent the wood chips from being damaged or deformed during the carbonization process, so as to obtain a stable three-dimensional ordered porous structure with uniform voids, especially to obtain smoother microchannels, so that highly active hydrotalcite nanosheets can grow evenly and densely on the carbonized wood skeleton, reduce the generation of dead materials, and better approach the active sites. In addition, the three-dimensional ordered porous structure is conducive to exposing more active sites, and can achieve good electrolyte ion penetration / accessibility and abundant gas transmission channels, thereby further improving the catalytic activity and stability of the electrocatalyst.
[0017] 4. In the method of the present invention, mannitol is added to the precursor solution and mixed with the carbonized wood substrate. During the reaction, due to the strong permeability of mannitol, when bubbles appear, it can penetrate into the bubbles, which can reduce the accumulation of bubbles or even eliminate the bubbles, so that the bubbles quickly leave the precursor solution, thereby enhancing the adhesion of the hydrotalcite on the nanosheets on the carbonized wood substrate. At the same time, under the combination of hydrothermal conditions, the synergistic effect with mannitol prevents the agglomeration of ions in the solution, so that the hydrotalcite can be more evenly and densely attached to the carbonized wood substrate, so as to obtain an electrocatalyst with high stability and high catalytic activity.
[0018] 5. The method of the present invention is simple and easy to operate, does not require annealing, and does not require the use of a binder during use, but still obtains an electrocatalyst with high catalytic activity and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a lateral scanning electron microscope image of the electrode prepared in Example 1 of the present invention; Figure 2 This is a longitudinal scanning electron microscope image of the electrode prepared in Example 1 of the present invention; Figure 3 The oxygen evolution polarization curves of the electrodes prepared in Example 1 and Comparative Examples 1-3 of the present invention are shown; Figure 4 This is a stability curve diagram of the electrode prepared in Example 1 of the present invention.
[0020] Figure 5 This is a stability curve diagram of different electrodes in Experimental Example 2 of the present invention.
[0021] Figure 6 This is a stability curve diagram of different electrodes in Experimental Example 3 of the present invention. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0023] A method for preparing a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst comprises the following steps: (1) Pretreatment: The basswood was cut into 200-300 mm × 150-200 mm × 1-2 mm basswood chips along the vertical direction of the tree growth, and ultrasonically cleaned at 50 kHz using ethanol and deionized water at a material-liquid ratio of 1:25 g / ml, each cleaning time was 25 min, and then placed in a 60°C vacuum drying oven for 8 h to obtain dry wood chips; (2) Preparation of carbonized wood: Dry wood chips were heated to 200°C at a rate of 5°C / min under air conditions and pre-carbonized at this temperature for 6 hours. Silicon carbide (0.5% by weight of the dry wood chips) was then mixed with the pre-carbonized wood chips and evenly mixed. The chips were then heated to 900°C under an argon gas rate of 1.0 L / min and kept warm for 7 hours. After cooling to room temperature, they were ultrasonically cleaned at 50 kHz using ethanol and deionized water in a material-liquid ratio of 1:25 g / ml. Each cleaning lasted 25 minutes. The chips were then placed in a 60°C vacuum drying oven and dried for 24 hours to obtain a carbonized wood substrate. (3) Preparation of precursor solution: Dissolve 0.4 mmol nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.4 mmol iron nitrate nonahydrate (Fe(NO3)3·9H2O), 0.06 mmol ruthenium chloride (RuCl3) and 6 mmol urea (CH4N2O) in 30 mL of deionized water and stir for 30 min to obtain a precursor solution. (4) Hydrothermal reaction: Take 0.8% of the weight of the precursor solution and mix it with the precursor solution. Then add the carbonized wood substrate according to the solid-liquid ratio of the carbonized wood substrate and the precursor solution of 0.1:25g / ml, and then put them into a 50mL high-pressure reactor. React at 100°C for 14h. Collect the product, and use ethanol and deionized water at a solid-liquid ratio of 1:25g / ml to ultrasonically clean it at 50kHz. Each ultrasonic cleaning lasts for 20min, and the cleaning is repeated 3 times. Put it into a vacuum drying oven at a drying temperature of 60°C and dry it for 24h to obtain a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst. Its lateral scanning electron microscope image is shown as follows: Figure 1 The longitudinal scanning electron microscope image is shown in Figure 2 shown.
[0024] The porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst in Example 1 was directly used as the anode working electrode and immersed in a 1.0 M KOH solution to perform a linear sweep voltammetry test of hydrogen evolution to characterize its electrocatalytic activity for hydrogen evolution reaction. Figure 3 As shown, at 100 mA cm -2 Under the current density, the overpotential of the porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution catalysis is only 300 mV, showing excellent electrocatalytic activity. In addition, the porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution catalyst in Example 1 was directly used as the anode working electrode and immersed in a 1.0M KOH solution for 50h chronopotentiometry test to determine its long-term stability. Figure 4 As shown, the voltage only increased by about 2.3% after 50h stability test, demonstrating the excellent stability of the catalyst. Example 2
[0025] A method for preparing a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst comprises the following steps: (1) Pretreatment: The basswood was cut into 200-300 mm × 150-200 mm × 1-2 mm basswood chips along the vertical direction of the tree growth, and ultrasonically cleaned at 50 kHz using ethanol and deionized water at a material-liquid ratio of 1:30 g / ml, each cleaning time was 20 min, and then placed in a 60°C vacuum drying oven for 8 h to obtain dry wood chips; (2) Preparation of carbonized wood: Dry wood chips were heated to 260°C at a rate of 5°C / min under air conditions and pre-carbonized at this temperature for 6 hours. Silicon carbide (0.8% by weight of the dry wood chips) was then mixed evenly with the pre-carbonized wood chips. The chips were then heated to 1000°C at an argon rate of 0.8 L / min and kept warm for 6 hours. After cooling to room temperature, the chips were ultrasonically cleaned at 50kHz using ethanol and deionized water in a material-liquid ratio of 1:20-30 g / ml for 20 minutes each time. The chips were then placed in a 60°C vacuum drying oven and dried for 24 hours to obtain a carbonized wood substrate. (3) Preparation of precursor solution: Dissolve 0.6 mmol nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.3 mmol iron nitrate nonahydrate (Fe(NO3)3·9H2O), 0.05 mmol ruthenium chloride (RuCl3) and 5 mmol urea (CH4N2O) in 30 mL deionized water and stir for 35 min to obtain a precursor solution. (4) Hydrothermal reaction: Take 0.5% of the weight of the precursor solution and mix it evenly with the precursor solution. Then add the carbonized wood substrate according to the solid-liquid ratio of carbonized wood substrate to precursor solution of 0.1:20 g / ml, and then put them into a 50 mL high-pressure reactor. React at 120 °C for 12 h. Collect the product, and use ethanol and deionized water at a solid-liquid ratio of 1:20 g / ml to ultrasonically clean it at 50 kHz. Each ultrasonic cleaning lasts for 25 min. Repeat the cleaning three times. Put it into a vacuum drying oven at a drying temperature of 60 °C and dry it for 24 h to obtain porous carbonized wood-supported ruthenium-based hydrotalcite nanosheets oxygen evolution electrocatalyst. Example 3
[0026] A method for preparing a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst comprises the following steps: (1) Pretreatment: The basswood was cut into 200-300 mm × 150-200 mm × 1-2 mm basswood chips along the vertical direction of the tree growth, and ultrasonically cleaned at 50 kHz using ethanol and deionized water at a material-liquid ratio of 1:20 g / ml, each cleaning time lasting 30 min, and then placed in a 60°C vacuum drying oven for drying for 8 h to obtain dry wood chips; (2) Preparation of carbonized wood: Dry wood chips were heated to 300°C at a rate of 5°C / min under air conditions and pre-carbonized at this temperature for 5 h. Silicon carbide (1.1% by weight of the dry wood chips) was mixed evenly with the pre-carbonized wood chips. The chips were then heated to 1100°C at an argon rate of 0.8 L / min and kept warm for 5 h. After cooling to room temperature, they were ultrasonically cleaned at 50 kHz using ethanol and deionized water at a material-liquid ratio of 1:20 g / ml. Each cleaning lasted 30 min. The chips were then placed in a 60°C vacuum drying oven and dried for 24 h to obtain a carbonized wood substrate. (3) Preparation of precursor solution: Dissolve 0.8 mmol nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.1 mmol iron nitrate nonahydrate (Fe(NO3)3·9H2O), 0.04 mmol ruthenium chloride (RuCl3) and 4 mmol urea (CH4N2O) in 30 mL of deionized water and stir for 20 min to obtain a precursor solution. (4) Hydrothermal reaction: Take 0.3% mannitol by weight of the precursor solution and mix it evenly with the precursor solution. Then add it to the carbonized wood substrate at a solid-liquid ratio of 0.1:30 g / ml, and then put them into a 50 mL high-pressure reactor. React at 200 °C for 10 h. Collect the product and use ethanol and deionized water at a solid-liquid ratio of 1:30 g / ml to ultrasonically clean it at 50 kHz. Each ultrasonic cleaning lasts for 30 min. Repeat the cleaning three times. Put it into a vacuum drying oven at a drying temperature of 60 °C for 24 h to obtain a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst.
[0027] Comparative Example 1 A method for preparing a foamed nickel-based hydrotalcite nanosheet oxygen evolution electrocatalyst comprises the following steps: (1) Pretreatment: First, the nickel foam is cut into a size of 200-300 mm × 150-200 mm × 1-2 mm, and ultrasonically cleaned in 3M hydrochloric acid, acetone, ethanol and deionized water in sequence, each ultrasonic cleaning time is 20 min, and then placed in a 60°C vacuum drying oven for 8 h to obtain dry nickel foam; (2) Preparation of precursor solution: Dissolve 0.4 mmol nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.4 mmol iron nitrate nonahydrate (Fe(NO3)3·9H2O), 0.06 mmol ruthenium chloride (RuCl3) and 6 mmol urea (CH4N2O) in 30 mL of deionized water and stir for 30 min to obtain a precursor solution. (3) Hydrothermal reaction: The dried nickel foam obtained in step (1) and the precursor solution in step (2) were placed in a 50 mL high pressure reactor at a material-liquid ratio of 0.1:25 g / ml, and reacted at 120°C for 12 h. The product was collected and ultrasonically cleaned at 50 kHz using ethanol and deionized water at a material-liquid ratio of 1:20-30 g / ml, and the cleaning was repeated 3 times. The product was placed in a vacuum drying oven at a drying temperature of 60°C for 24 h to obtain a foamed nickel-based hydrotalcite nanosheet oxygen evolution electrocatalyst.
[0028] Comparative Example 2 A method for preparing a carbon paper-based hydrotalcite nanosheet oxygen evolution electrocatalyst comprises the following steps: (1) Pretreatment: First, the hydrophilic carbon paper was cut into a size of 200-300 mm × 150-200 mm, and ultrasonically cleaned in acetone, ethanol and deionized water in turn, each ultrasonic cleaning time was 20 min, and then placed in a 60 ° C vacuum drying oven for 8 h to obtain dry carbon paper; (2) Preparation of precursor solution: Dissolve 0.4 mmol nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.4 mmol iron nitrate nonahydrate (Fe(NO3)3·9H2O), 0.06 mmol ruthenium chloride (RuCl3) and 6 mmol urea (CH4N2O) in 30 mL of deionized water and stir for 30 min to obtain a precursor solution. (3) Hydrothermal reaction: The dried carbon paper obtained in step (1) and the precursor solution in step (2) were placed in a 50 mL high pressure reactor at a solid-liquid ratio of 0.1:25 g / ml, and reacted at 120°C for 12 h. The product was collected and ultrasonically cleaned at 50 kHz using ethanol and deionized water at a solid-liquid ratio of 1:20-30 g / ml, and the cleaning was repeated 3 times. The product was placed in a vacuum drying oven at a drying temperature of 60°C for 24 h to obtain a carbon paper-based hydrotalcite nanosheet oxygen evolution electrocatalyst.
[0029] Comparative Example 3 A method for preparing a carbon cloth-based hydrotalcite nanosheet oxygen evolution electrocatalyst comprises the following steps: (1) Pretreatment: First, the carbon cloth was cut into a size of 200-300 mm × 150-200 mm, and ultrasonically cleaned in acetone, ethanol and deionized water in turn, each ultrasonic cleaning time was 20 min, and then placed in a 60 ° C vacuum drying oven for 8 h to obtain a dry carbon cloth; (2) Preparation of precursor solution: Dissolve 0.4 mmol nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.4 mmol iron nitrate nonahydrate (Fe(NO3)3·9H2O), 0.06 mmol ruthenium chloride (RuCl3) and 6 mmol urea (CH4N2O) in 30 mL of deionized water and stir for 30 min to obtain a precursor solution. (3) Hydrothermal reaction: The dried carbon cloth obtained in step (1) and the precursor solution in step (2) were placed in a 50 mL high-pressure reactor at a solid-liquid ratio of 0.1:25 g / ml, and reacted at 120°C for 12 h. The product was collected and ultrasonically cleaned at 50 kHz using ethanol and deionized water at a solid-liquid ratio of 1:20-30 g / ml. The cleaning was repeated 3 times, and the product was placed in a vacuum drying oven at a drying temperature of 60°C for 24 h to obtain a carbon cloth-based hydrotalcite nanosheet oxygen evolution electrocatalyst.
[0030] Test Example 1 In order to verify the effect of different carriers on the performance of electrocatalysts, the following different groups of experiments were set up: (1) Embodiment 1; (2) Comparative Example 1; (3) Comparative Example 2; (4) Comparative example 3.
[0031] The electrocatalysts of the above groups were directly used as anode working electrodes and immersed in 1.0 M KOH solution to carry out linear sweep voltammetry test of hydrogen evolution. The results are shown in Figure 3 .
[0032] like Figure 3 As shown, from Figure 3 It can be seen that at 100mA cm -2 At the current density of 100 mA cm, the overpotential of the electrocatalyst of Example 1 was only 300 mV, showing excellent electrocatalytic activity; while Comparative Examples 1-3 used different carriers and obtained 100 mA cm -2 At a current density, a higher overpotential is required. Therefore, it is shown that the carbonized wood substrate used in the present invention as a carrier of the catalytically active component to prepare the electrocatalyst has a higher electrocatalytic activity.
[0033] Test Example 2 In order to verify the effect of carbonized wood modified with different silicon carbide contents on the final performance of the electrocatalyst, the following different groups were set up: Table 1 Silicon carbide content corresponding to different groups Group Silicon carbide as a percentage of dry wood chips weight Comparative Example 4 0% Example 1 Group 0.5% Example 4 Group 0.8% Example 5 Group 1.1% Comparative Example 5 1.4% Note: Except for the percentage of silicon carbide in the weight of the dried wood chips in each group, the other steps and parameters are the same as those in Example 1.
[0034] (1) The electrocatalysts of the above groups were directly used as anode working electrodes and immersed in 1.0 M KOH solution for hydrogen evolution linear sweep voltammetry test. The analysis results are shown in Table 2.
[0035] Table 2 Overpotential of different groups at different current densities in Table 1 Group <![CDATA[50 mA cm -2 Overpotential / mV]]> <![CDATA[100 mA cm -2 Overpotential / mV]]> Comparative Example 4 368 479 Example 1 Group 273 298 Example 4 Group 286 311 Example 5 Group 281 306 Comparative Example 5 301 374 It can be seen from Table 2 that as the percentage of silicon carbide in the weight of dry wood chips increases, the required overpotential at different current densities first decreases and then increases, indicating that the best catalytic activity can be obtained within the percentage range of silicon carbide in the weight of dry wood chips of the present invention, and that too low or too high an amount of silicon carbide added will affect the final catalytic activity of the electrocatalyst.
[0036] (2) The different porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution catalysts in Table 1 were directly used as anode working electrodes and immersed in 1.0 M KOH solution for 50 h of chronopotentiometry test to determine their long-term stability. The results are shown in Table 1. Figure 5 shown.
[0037] from Figure 5 It can be seen that after 50 hours of stability testing, the voltage of Example 1, Example 4 and Example 5 was stable, and only increased by 2.3-2.9%, indicating that when the amount of silicon carbide added was within the scope of the present invention, the prepared electrocatalyst had excellent stability. When the amount of silicon carbide added exceeded the scope of the present invention and after 50 hours of stability testing, the voltage increased by 25%-30%, indicating that the amount of silicon carbide added in the present invention significantly affected the stability of the final electrocatalyst.
[0038] Test Example 3 In order to verify the effect of different mannitol addition amounts on the final performance of the electrocatalyst, the following different groups were set up: Table 3 Precursor treatment conditions of different groups Group Precursor fluid treatment Comparative Example 5 No mannitol Example 6 Group Mannitol accounts for 0.3% of the precursor solution weight Example 1 Group Mannitol accounts for 0.8% of the precursor solution weight Comparative Example 6 Mannitol accounts for 1.1% of the precursor solution weight Comparative Example 7 Mannitol replaced with pentaerythritol Note: Except for the different precursor solution treatment conditions, the other steps and parameters of each group are the same as those of Example 1.
[0039] (1) The above-mentioned electrocatalysts were directly used as anode working electrodes and immersed in 1.0 M KOH solution for hydrogen evolution linear sweep voltammetry test. The analysis results are shown in Table 4.
[0040] Table 4 Overpotential of different groups at fixed current density in Table 3 Group <![CDATA[100 mA cm -2 Overpotential / mV]]> Comparative Example 5 515 Example 6 Group 301 Example 1 Group 295 Comparative Example 6 442 Comparative Example 7 474 It can be seen from Table 4 that different precursor solution treatment conditions ultimately affect the catalytic performance of the electrocatalyst. Comparative Example 5 does not contain mannitol. When the concentration reaches 100 mA cm -2When the current density is high, a higher overpotential is required, because in the hydrothermal reaction, as the temperature increases, water may partially volatilize to form bubbles, and when the speed at which the bubbles discharge the precursor liquid is lower than the speed at which the active components are loaded on the carbonized wood substrate, the bubbles are easily accumulated, resulting in holes or cracks in the catalyst layer, and also interfering with the uniform distribution of the active components, easily making the electrocatalyst inactivated during the catalytic process, increasing dead materials, so the activity of the electrocatalyst is reduced; and when the mannitol content increases beyond the scope of the present invention, during the hydrothermal reaction, it may cause local crystal growth to be too fast, reducing the integrity of the electrocatalyst, and reducing the catalytic activity of the electrocatalyst; when mannitol is replaced with pentaerythritol, due to the poor permeability of pentaerythritol, when the speed at which the bubbles discharge the precursor liquid is lower than the speed at which the active components are loaded on the carbonized wood substrate, the bubbles are easily accumulated, resulting in holes or cracks in the catalyst layer, and also interfering with the uniform distribution of the active components, easily making the electrocatalyst inactivated during the catalytic process, increasing dead materials, so the activity of the electrocatalyst is reduced. And in the method of the present invention, during the hydrothermal reaction, adding a certain amount of mannitol can improve the activity of the electrocatalyst.
[0041] (2) The different porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution catalysts in Table 3 were directly used as anode working electrodes and immersed in 1.0 M KOH solution for 50 h of chronopotentiometry test to determine their long-term stability. The results are shown in Table 3. Figure 6 shown.
[0042] from Figure 6 It can be seen that the voltage of Example 1 and Example 6 groups was stable after 50h stability test, and only increased by 2.3-2.7%, indicating that the amount of mannitol added was within the scope of the present invention, and the prepared electrocatalyst had excellent stability. However, when the amount of mannitol added exceeded the scope of the present invention or no mannitol was added or mannitol was replaced with pentaerythritol, the voltage increased by 40%-50% after 50h stability test, indicating that the amount of mannitol added and whether it was added significantly affected the stability of the final electrocatalyst.
[0043] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A method for preparing a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst, characterized in that: The following steps are involved: (1) Pretreatment: The basswood was cut into wood chips, which were ultrasonically treated with deionized water and ethanol in sequence and then vacuum dried to obtain dry wood chips; (2) Preparation of carbonized wood: pre-carbonizing the dried wood chips, calcining them under inert gas protection, ultrasonically treating them with deionized water and ethanol, and then vacuum drying them to obtain a carbonized wood substrate; (3) Preparation of precursor solution: dissolve nickel nitrate hexahydrate, iron nitrate nonahydrate, ruthenium trichloride and urea in deionized water and stir well to obtain a precursor solution; (4) Hydrothermal reaction: The carbonized wood substrate in step (2) and the precursor solution in step (3) are mixed and placed in a high-pressure reactor for hydrothermal reaction. After cooling to room temperature, the product is collected, and ultrasonically cleaned repeatedly with deionized water and ethanol, and dried to obtain a porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst.
2. The method for preparing the porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: In the step (1), the material-liquid ratio of basswood to deionized water or ethanol is 1:20-30 g / ml; in the step (2), the material-liquid ratio of calcined wood chips to deionized water or ethanol is 1:20-30 g / ml; in the step (4), the material-liquid ratio of the product to deionized water or ethanol is 1:20-30 g / ml; in the steps (1), (2) and (4), each ultrasonic cleaning time is 20-30 min.
3. The method for preparing the porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: In the step (1), the wood chips have a length of 200-300 mm, a width of 150-200 mm, and a thickness of 1-2 mm.
4. The method for preparing the porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: In the step (2), the dried wood chips are pre-carbonized in air at 200-300° C. for 5-6 hours.
5. The method for preparing the porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst as claimed in claim 4, characterized in that: In the step (2), after pre-carbonization, 0.5-1.1% of the weight of the dry wood chips is mixed with silicon carbide and the pre-carbonized wood chips, and then calcined under the protection of inert gas.
6. The method for preparing the porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: In the step (2), calcination is performed for 5 to 7 hours at a temperature of 900 to 1100° C. and an argon gas flow rate of 0.8 to 1.0 L / min.
7. The method for preparing the porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: The step (3) is specifically as follows: 0.4-0.8 mmol nickel nitrate hexahydrate, 0.1-0.4 mmol iron nitrate nonahydrate, 0.04-0.06 mmol ruthenium trichloride and 4-6 mmol urea are dissolved in 30 mL deionized water, and stirred for 20-35 min to obtain a precursor solution.
8. The method for preparing the porous carbonized wood-supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: The material-liquid ratio of the carbonized wood substrate in step (4) to the precursor liquid in step (3) is 0.1:20-30 g / ml.
9. The method for preparing the porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: In the step (4), the hydrothermal conditions are: reacting at 100-200° C. for 10-14 hours.
10. The method for preparing the porous carbonized wood supported ruthenium-based hydrotalcite nanosheet oxygen evolution electrocatalyst according to claim 1, characterized in that: In the step (4), before the precursor liquid is mixed with the carbonized wood substrate in the step (2), 0.3-0.8% of mannitol by weight of the precursor liquid is added to the precursor liquid and mixed evenly.
Citation Information
Patent Citations
Preparation method of nano-material with bismuth oxybromide loaded on cobalt nickel hydrotalcite surface
CN105217720A
Wood-based hydrogen evolution electrode and preparation method thereof
CN113106482A
Monatomic ruthenium-loaded ferronickel bimetallic hydrotalcite material, and preparation method and application thereof
CN114031128A
Silver / cobalt ferrite double-doped wood charcoal oxygen evolution catalyst and preparation method thereof
CN117822014A
Method for growing BCN nanotube in wood-derived carbon pore channel and application of BCN nanotube
CN117985711A